Dietary intervention of prebiotic partially hydrolyzed guar gum improves skin viscoelasticity, stratum corneum hydration, and ‍reduction of trans-epidermal water loss: a ‍randomized, double-blind, and placebo-controlled clinical study in healthy humans - Kapoor, Mahendra P.; Abe, Aya; Morishima, So; Nakajima, Atsushi; Ozeki, Makoto; Sato, Norio (Journal of Clinical Biochemistry and Nutrition, 2025)
Dietary fiber-rich diets are gaining popularity as an alternative therapy for skin health. Plant-based prebiotic partially hydrolyzed guar gum (PHGG) dietary fiber promotes gastrointestinal health, which is imperative for skin health through the gut microbiome. In this randomized, double-blind, and placebo-controlled study, the purpose was to assess the therapeutic effects of PHGG on skin hydration, trans-epidermal water loss (TEWL), and skin viscoelastic properties during the winter season. Healthy male and female subjects (n ‍= 70; 9 male and 61 female; mean age: 45.5 ‍± 8.1 years) were recruited. They received either the 5 ‍‍g PHGG dietary fiber (n ‍= 35) or a 5 ‍‍g placebo (n = 35) for twelve weeks. Skin moisture, TEWL, skin elasticity and skin color parameters, and related features were assessed at baseline, after 6 and 12 weeks, and questionnaires to evaluate the study outcomes. The results confirmed the improvement in skin conditions throughout the winter season by restoring skin hydration, reducing TEWL, and improving skin elasticity parameters. After 6 weeks of PHGG intake, there was a substantial decrease in TEWL and improvement in viscoelasticity metrics when compared to placebo. Subject satisfaction with efficacy reflected these encouraging findings, and PHGG was well tolerated, with no adverse events occurring during the study period.